Discovery of BRAF/HDAC Dual Inhibitors Suppressing Proliferation of Human Colorectal Cancer Cells - Li, Yingjun; Huang, Yongjun; Cheng, Huimin; Xu, Fang; Qi, Ruxi; Dai, Botao; Yang, Yujian; Tu, Zhengchao; Peng, Lijie; Zhang, Zhang (Frontiers in Chemistry, 2022)
Based on the favorable interaction between histone deacetylases (HDACs) and BRAF inhibitors, a series of (thiazol-5-yl)pyrimidin-2-yl)amino)-N- hydroxyalkanamide derivatives were designed and synthesized as novel dual inhibitors of BRAF kinase and HDAC by using pharmacophore hybrid strategy. In particular, compound 14b possessed potent activities against BRAF, HDAC1 and HDAC6 enzymes. 14b potently suppressed the proliferation of HT-29 cells harboring BRAFV600E mutation as well as HCT116 cells with wild type BRAF. The dual inhibition against BRAF and HDACs downstream proteins was validated in both cells. Collectively, the results support 14b as a promising lead molecule for further development and a useful tool for studying the interaction of RAF/MEK/ERK pathway and epigenetics.